(untitled) (International Journal of Management and Sustainability, 2024)
This study aims to explore the relationship between digital marketing and business performance and sustainability in small-medium enterprises (SMEs) in Bandung, Indonesia. Additionally, it examines the mediation power of business performance in enhancing the association of digital marketing, intellectual capital, and business sustainability. We employed a quantitative approach and acquired data from 308 SMEs in Bandung, Indonesia. Data collection utilized Google Forms and purposive sampling methods. We tested the hypotheses using Smart PLS. The results indicate that digital marketing has no significant effect on business performance. However, we found that intellectual capital acts as a catalyst for both business performance and sustainability. Given the identified role of intellectual capital as a catalyst for both business performance and sustainability, SMEs owners should prioritize investments in knowledge creation by providing employee training, fostering a culture of continuous learning, and supporting research and development initiatives. Investments in knowledge creation and innovation are crucial for SMEs to enhance business performance and sustainability. This involves providing employee training, fostering a culture of continuous learning, and supporting research and development initiatives.